An aquatic microhymenopterous egg-parasitoid of Argia insipida Hagen in Selys (Odonata: Coenagrionidae) and biological observations in the Central Amazon, Brazil - Querino, Ranyse Barbosa (2009)
The tritrophic interaction Argia insipida Hagen in Selys, the Trichogrammatidae egg parasitoid Pseudoligosita longifrangiata (Viggiani) and the host plant Tonina fluviatilis (Eriocaulacea), which is a substrate for egg deposition of A. insipid, was investigated. The study locality was a stream with rapids where macrophytes such as T. fluviatilis grow. Information on aquatic egg parasitoids is scarce. This is the first record of egg parasitism of A. insipida by P. longifrangiata in Brazil, and the first record of occurrence of P. longifrangiata in the country. Parasitized and unparasitized eggs of A. insipida were observed only on leaves 0-5 cm below the water surface. The maximum number of pairs of A. insipida laying eggs in the study area was observed between 13:00h and 14:00h. Leaves of T. fluviatilis become yellowish and dry out when large numbers of eggs of A. insipida are laid on them.